DETECTION OF EMISSION OF HAZARDOUS SUBSTANCES (VOC) IN ENVIRONMENTAL TECHNICAL EDUCATION - RUŽINSKÁ, Eva (Trends in education, 2010)
The paper deals with specifying the effective detection of VOC analysers (FID, PID), used for continous monitoring of hazardous substances in industrial technologies and activities generating volatile organic compound rise to suggestions for technical solution to their reduction.
Keywords: hazardou substances - VOC; analysers; technical education; environment.